Advanced damage modelling for seismic assessment of timber structure - Sirumbal Zapata, Luis Fernando (2018)
Throughout this thesis, advanced numerical tools and laboratory tests are investigated that will allow an accurate prediction of the global nonlinear structural response of hybrid timber-steel connections under cyclic loading. The conceptual development of the model, its mathematical formulation, numerical coding and implementation in a commercial FE software are documented in this thesis. Furthermore, the proposed timber material model has been developed within the framework of the Continuum Damage Mechanics (CDM) theory, making it ideal for damage evolution modelling and behaviour-based seismic assessment of timber structures. Experimental studies available in the literature were employed to assess the accuracy and overall performance of the proposed constitutive model at the material and structural (or component) level. Additional local responses not easily identifiable from the experiments, such as potential internal cracking and crushing zones, damage extent or plastic deformation magnitudes, were obtained from the 3D continuum model. The proposed new plasticity-damage model captures for the first time the key features of nonlinear cyclic behavior of wood at both material and component levels, including: i) cyclic degradation of stiffness and strength, ii) local brittle failure due to tensile and shear stresses, iii) local ductile failure due to compressive stresses, iv) stiffness recovery upon load reversal (crack opening and closing), and v) permanent plastic deformation due to compressive stresses.